Three New Paintings by Victor Wolfvoet in the Footsteps of Rubens and Van Dyck - Matías Díaz Padrón (Philostrato, 2021)
This article adds three new paintings to Victor Wolfvoet´s catalogue. These paintings were previously confusedly attributed to the workshop of Rubens and to other painters such as Peter Thys and Willem van Herp. This study contributes to defining the personality of this painter closely linked to Peter Paul Rubens y Anton van Dyck, whose compositions he reproduced in small format and with a well-defined style.